2006
DOI: 10.1007/s00253-005-0262-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of n-alkanes by a newly isolated strain of Acinetobacter venetianus: the role of two AlkB-type alkane hydroxylases

Abstract: A bacterial strain capable of utilizing n-alkanes with chain lengths ranging from decane (C10H22) to tetracontane (C40H82) as a sole carbon source was isolated using a system for screening microorganisms able to grow on paraffin (mixed long-chain n-alkanes). The isolate, identified according to its 16S rRNA sequence as Acinetobacter venetianus, was designated A. venetianus 6A2. Two DNA fragments encoding parts of AlkB-type alkane hydroxylase homologues, designated alkMa and alkMb, were polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 29 publications
1
50
0
2
Order By: Relevance
“…Consumption of n-triacontane is more rapid than that of n-hexadecane, in contrast with lower biomass accumulation on the longest alkane. It appears that the efficiency of the AH system is reduced with increasing chain length, as previously reported for other strains (5,20,21,24,28).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Consumption of n-triacontane is more rapid than that of n-hexadecane, in contrast with lower biomass accumulation on the longest alkane. It appears that the efficiency of the AH system is reduced with increasing chain length, as previously reported for other strains (5,20,21,24,28).…”
Section: Resultssupporting
confidence: 64%
“…Growth of SoCg on triacontane would be poorer that that on hexadecane for this reason and also because a second, unknown system, that is functional on C 16 but not on C 30 , would contribute to overcome the limiting step of n-alkane degradation on C 16 . The alkane hydroxylase, in fact, catalyzes the initial attack and determines the size range of n-alkanes to be degraded; its specific activity is generally reduced with increasing chain length (5,20,21,24,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggested that stearyl alcohol induces expression of many extracellular proteins and prompted us to investigate the multiple aspects of NT80 cells' response to stearyl alcohol. Several previous studies reported the effects of methanol and ethanol on bacterial cells (Hendrickson et al, 2010;Lu et al, 2012) and several other studies examined the mechanism of assimilation of n-alkanes by bacteria (Bouchez Naïtali et al, 1999;Tani et al, 2001;Throne-Holst et al, 2006). The effects of fatty alcohols on bacterial cells, however, have hardly been explored.…”
Section: Introductionmentioning
confidence: 98%
“…S14-10 [19] 、Geobacillus thermodenitrificans NG80 [20] 等菌株的烷烃降解酶系和相关基因。已 报道的 AlkBs 和 CYP153s 都是负责中等链长烷烃 (C 5~C12 )的降解,对于长链烷烃羟化酶 AlmA 和 LadA 的报道却不多见。Maier T 等人 [21] 从 Acinetobacter calcoaceticus EB104 克隆到了参与烷烃羟化的 P450 基 因。Mimmi Throne-Holst 等人 [22,23] …”
unclassified